Sufficient conditions for the existence of an optimal solution to a control problem for integro-differential equation in Banach spaces - Radchyn, Yevhenii; Kichmarenko, Olga (Запоріжжя : ТДАТУ, 2026)
EN: This work examines an optimal control problem for a class of integrodifferential equation parabolic type in a Banach space. Sufficient conditions on the coefficients are established to guaranty the existence of optimal pairs. In our case, the main problem of optimal control is considered up to the time of existence of the solution from the fixed domain, which distinguishes the analyzed problem from other investigations.
Keywords: optimal control; weakly convergence; unbounded operator; semigroup; minimizer; fixed point